The effect of strategic intelligence in customer relationship management: An analytical study of the opinions of a sample of administrative leaders in some private banks in Baghdad (Entrepreneurship Journal for Finance and Business, 2022)
This research aims to know the role that strategic intelligence performed in its dimensions (forecasting, organized thinking, partnership, invention, and benchmarking) in influencing customer relationship management in its dimensions (customer acquisition, strengthening the relationship with the customer, customer retention, customer satisfaction) for a sample of private banks In the province of Baghdad, the two researchers relied on the questionnaire as a measure of the research variables, and the relationship between them was tested by selecting intentional sample that included (106) of (principals of senior departments - departments - and administrative units) working in the banking sector using statistical methods(SPSS, v.25) The results showed a direct impact relationship of strategic intelligence in managing customer relations, and the increasing interest of the surveyed banks in strengthening the relationship with the customer, which was one of its most prominent goals, and the research reached to a number of recommendations, most notably working on paying attention to strategic intelligence and activating its role among banking leaders to support invention capabilities and improve the reality of banking services.